2016
DOI: 10.18097/pbmc20166201022
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity and mechanisms of therapeutic action of rosmarinic acid, luteolin and its sulphated derivatives

Abstract: Обобщены результаты недавних экспериментальных исследований биологической активности и механизмов лечебного действия розмариновой кислоты, лютеолина и его сульфатированных производных при заболеваниях, связанных с нарушением углеводного и липидного обмена. Особое внимание уделено данным, показывающим высокий терапевтический потенциал этих соединений при профилактическом и лечебном применении при экспериментальном сахарном диабете 2-го типа и гиперлипидемии. На основании анализа полученных нами результатов и ли… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…When used for therapeutic purposes, RA, LT and DSL have unique features regarding the mechanism of their anti-inflammatory and antioxidant activity; of note, PPC exerted a more pronounced pharmacological effect than its major components, RA, LT and DSL, applied separately. For this reason, the use of combined pharmaceutical agents as PPC (5,26), acting on several different targets in cells, appears to be a promising approach for development of remedies of complementary therapy for preventing and treating multifactorial metabolic diseases. This approach may overcome the abovementioned problems regarding undesirable side effects of potent synthetic PPAR agonists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When used for therapeutic purposes, RA, LT and DSL have unique features regarding the mechanism of their anti-inflammatory and antioxidant activity; of note, PPC exerted a more pronounced pharmacological effect than its major components, RA, LT and DSL, applied separately. For this reason, the use of combined pharmaceutical agents as PPC (5,26), acting on several different targets in cells, appears to be a promising approach for development of remedies of complementary therapy for preventing and treating multifactorial metabolic diseases. This approach may overcome the abovementioned problems regarding undesirable side effects of potent synthetic PPAR agonists.…”
Section: Discussionmentioning
confidence: 99%
“…These pathological constituents subsequently lead to changes in the structural and functional organization of the membranes and the formation of various pathological processes. Therefore, due to their anti-inflammatory and antioxidant actions, the major components of PPC, RA, LT and its sulfated derivatives, may be utilized for the treatment of MS and T2D (26,27). PPC and its main components showed a high degree of safety and lack of side effects (8,26).…”
Section: Antiinflammatory and Antioxidant Activity Of Ra Lt And Its mentioning
confidence: 99%
“…SAA has protective effects on acute kidney injury induced by ischemia-reperfusion injury [ 14 ] and can greatly attenuate monocrotaline-induced hypertrophic damage of the myocardium, parenchymal injury, and collagen deposition in the lungs [ 15 ]. RA reportedly has a therapeutic effect on type 2 diabetes and hyperlipidaemia [ 16 ]. Studies have shown that CAA ameliorates cardiac damage in isoproterenol-induced myocardial infarction by maintaining lipid peroxide metabolism because of its free radical scavenging and antioxidant effects [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zosteracea species have been found to be widely distributed along different regions, such as temperate North Atlantic, temperate North Pacific, temperate Southern Ocean and Mediterranean [123]. Polyphenol complex from Zosteraceae mainly consists of rosmarinic acid, luteolin, and luteolin disulfate [133]. The polyphenol complex was tested against highly pathogenic strain of the Tick-borne encephalitis (TBE) virus of the Far-Eastern subtype Dalinegorsk (Dal), on porcine embryo kidney (SPEV) cells.…”
Section: Seagrassesmentioning
confidence: 99%